Direct measurement of water states in cryopreserved cells reveals tolerance toward ice crystallization - Hübinger, Jan; Grabenbauer, Markus (Biophysical journal, 2016)
Complex living systems such as mammalian cells can be arrested in a solid phase by ultrarapid cooling. This allows for precise observation of cellular structures as well as cryopreservation of cells. The state of water, the main constituent of biological samples, is crucial for the success of cryogenic applications. Water exhibits many different solid states. If it is cooled extremely rapidly, liquid water turns into amorphous ice, also called vitreous water, a glassy and amorphous solid. For cryo-preservation, the vitrification of cells is believed to be mandatory for cell survival after freezing. Intracellular ice crystallization is assumed to be lethal, but experimental data on the state of water during cryopreservation are lacking. To better understand the water conditions in cells subjected to freezing protocols, we chose to directly analyze their subcellular water states by cryo-electron microscopy and tomography, cryoelectron diffraction, and x-ray diffraction both in the cryofixed state and after warming to different temperatures. By correlating the survival rates of cells with their respective water states during cryopreservation, we found that survival is less dependent on ice-crystal formation than expected. Using high-resolution cryo-imaging, we were able to directly show that cells tolerate crystallization of extra- and intracellular water. However, if warming is too slow, many small ice crystals will recrystallize into fewer but bigger crystals, which is lethal. The applied cryoprotective agents determine which crystal size is tolerable. This suggests that cryoprotectants can act by inhibiting crystallization or recrystallization, but they also increase the tolerance toward ice-crystal growth.